METHODS OF DEVELOPING SPORTS ACTIVITIES BASED ON INTERNATIONAL TRENDS IN ORGANIZING THE EDUCATIONAL PROCESS IN HIGHER EDUCATION - Aminov Botir Umidovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article analyzes the methods of developing sports exercises in the organization of the educational process in higher education based on international trends.